Pile Driving Effects on Nearby Building - Musir, Adhilla Ainun; Abdul Ghani, Abdul Naser (2013)
Piles are used to support many major structures such as buildings and bridges. It is known that pile driving activity creates vibrations in the ground and may affect nearby building and structure. However, the different pile size and shape as well as installation distances factors remain as interesting subjects for studies. The effect of hammer driven piles installation were studied using laboratory scale model. Three main effects were studied in which they are the response on top and bottom of a building, the vibration creates by three different distances of driven pile and the vibration produced by two different pile sizes.It can be concluded that the effect of vibrations are higher at the bottom of the building. The result also indicates that the nearest distance of piling activity produced higher vibration. However, it is interesting to note that the smaller pile creates larger vibrations.